Polymer capsule for self-repairing of organic waterproof material and preparation method of polymer capsule

By adopting a double-wall polymer capsule, combined with a highly absorbent resin and a silane coupling agent, the problem of cracks in organic waterproof materials being prone to long-term use is solved, and efficient self-repair effect is achieved and the service life of the material is extended.

CN119799055APending Publication Date: 2025-04-11ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510000421.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing organic waterproof materials are prone to cracks during long-term use and climate change, resulting in moisture infiltration, resulting in waterproofing performance failure, and the repair efficiency of existing capsule materials is inefficient.

Method used

Polyurethane produced by polytetrahydrofuran glycol and 2,4 toluene diisocyanate as raw materials is used as the inner capsule wall, and polyester resin is used as the outer capsule wall material to form a polymer capsule with a double-wall structure, and a highly absorbent resin and a silane coupling agent are added to the capsule to improve the stability and repair efficiency of the capsule.

Benefits of technology

It achieves high stability and high repair efficiency of polymer capsules, can effectively repair micro-cracks of organic waterproof materials, extend the service life of the material, and quickly respond to repair when cracks appear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224836370000081
    Figure BDA0005224836370000081
  • Figure BDA0005224836370000091
    Figure BDA0005224836370000091
  • Figure BDA0005224836370000101
    Figure BDA0005224836370000101
Patent Text Reader

Abstract

The invention belongs to the field of preparation of capsule materials, and relates to a polymer capsule for self-repairing of an organic waterproof material and a preparation method thereof. According to the polymer capsule, polyurethane generated by polymerization of polytetrahydrofuran glycol and 2, 4 toluene diisocynate is used as an inner-layer capsule wall, polyester resin is used as an outer-layer capsule wall material, and the double-wall structure material has good mechanical properties and mechanical stability and can stably exist in waterproof paint to protect a capsule core material, namely super absorbent resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of capsule material preparation, and relates to a polymer capsule for self-repairing of an organic waterproof material and a preparation method thereof. Background Art

[0002] At present, the capsules of organic waterproof materials usually use adhesive as the core material. When cracks appear in the organic waterproof material, the capsules break under the stress at the tip of the crack to release the adhesive to repair the crack. However, this method generally requires adding a catalyst to the organic waterproof material to cross-link and solidify the adhesive released by the capsule core, which is complicated to operate, and the catalyst will fail during long-term service, resulting in low repair efficiency. At the same time, organic waterproof materials are prone to cracks under the long-term influence of the climate environment, causing moisture to invade the matrix through the cracks, causing the waterproof material to fail and affecting the performance of the matrix.

[0003] Therefore, improving the stability and repair efficiency of organic waterproof materials is a technical problem to be solved. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a polymer capsule for self-repairing of organic waterproof materials and a preparation method thereof, wherein the polymer capsule has good stability and high repair efficiency.

[0005] The technical solution adopted by the present invention is:

[0006] A polymer capsule for self-repairing of an organic waterproof material. The raw materials used are, by weight, 20-40 parts of polytetramethylene glycol (PTMG), 20-40 parts of 2,4-toluene diisocyanate (TDI), 10-20 parts of a chain extender, 10-20 parts of a super absorbent resin (SAP), 30-60 parts of a polyester resin, 20-40 parts of an emulsifier, 20-40 parts of a dispersant, 10-15 parts of a coupling agent, 50-80 parts of a methanol solution and 40-80 parts of an organic solvent.

[0007] The size of the polymer capsules is 100-300 microns.

[0008] The chain extender is one or more of 1,4-butanediol (BOD), 1,6-hexanediol (HDO), and polyethylene glycol (PEG).

[0009] The component of the super absorbent resin (SAP) is polyacrylamide; the polyester resin is one or more of polyethylene terephthalate and polybutylene terephthalate.

[0010] The emulsifier is one or more of gum arabic, Span 40, Span 60, Tween 20, Tween 40, and polyvinyl alcohol; the dispersant is sodium alginate; the coupling agent is a silane coupling agent; and the organic solvent is one or more of xylene, acetone, and toluene.

[0011] The concentration of the methanol solution is 30%-40%.

[0012] A method for self-repairing polymer capsules for organic waterproof materials, comprising the following steps:

[0013] 1) Weigh each raw material according to the proportion;

[0014] 2) polytetrahydrofuran diol and 2,4 toluene diisocyanate are mixed and prepared as performed polymer for standby use;

[0015] Specific operation: Use a magnetic stirrer at 100-500r / min and 80-90℃ to stir for 5-10min to mix evenly to obtain the prepolymer for use;

[0016] 3) Add the emulsifier and dispersant to the methanol solution, stir at 100-500r / min and 80-90℃ for 5-10min to mix;

[0017] 4) adding the highly absorbent resin to the solution obtained in 3) and stirring at 100-500 r / min for 10-20 min to mix well;

[0018] 5) adding the chain extender to the solution obtained in 4) and stirring at 100-500 rpm for 10-20 min to mix well;

[0019] 6) adding the prepolymer obtained in 2) to the solution obtained in 5) and stirring at 600-1000 r / min for 1-3 h, filtering, washing the solid twice with deionized water, and drying to obtain particles A;

[0020] 7) Add the polyester resin to the organic solvent, stir at 600-1000r / min and 80-90°C for 5-10min, and mix well;

[0021] 8) Add the coupling agent to the solution obtained in 7), stir at 600-1000 r / min and 80-90° C. for 5-10 min, and mix well;

[0022] 9) placing the particles A obtained in 6) in the solution obtained in 8) and continuing stirring for 1-3 hours, filtering and drying the solid matter to obtain a polymer capsule for self-repairing of an organic waterproof material.

[0023] During the drying in step 6) and step 9), the product is placed in a blast drying oven and dried at 40-60°C for 12-24 hours. Compared with the prior art, the beneficial technical effects of the present invention are:

[0024] 1. The present invention uses polytetrahydrofuran diol and 2,4-toluene diisocyanate as raw materials to generate polyurethane as the inner layer capsule wall, and polyester resin as the outer layer capsule wall material. The double-wall structural material has good mechanical properties and mechanical stability, can stably exist in waterproof coatings, and protect the capsule core material super absorbent resin.

[0025] 2. In the polymerization reaction of polytetramethylene glycol and 2,4-toluene diisocyanate, the hydroxyl group (-OH) of polytetramethylene glycol and 2,4-toluene diisocyanate reacts with the isocyanate group (-NCO) of TDI. The hydrogen of the hydroxyl group is added to the nitrogen atom of the isocyanate group to form a urethane group, while releasing carbon dioxide. In the polymerization reaction, the molecular weight and properties of the polymer are controlled by adding a chain extender.

[0026] 3. The present invention uses super absorbent resin (SAP) as the capsule core material. This capsule core material has a high water absorption rate and a high expansion rate. Compared with other capsules that use adhesives and catalysts to cross-link and cure to repair cracks after rupture, the capsules of the present invention absorb water and swell immediately when in contact with water, thereby sealing the cracks, and the response is timely.

[0027] 4. The present invention uses silane coupling agent as coupling agent. The silane coupling agent forms chemical bonds with polyurethane and polyester resin, which can significantly increase the bonding stability between the inner layer capsule wall and the outer layer capsule wall. The silane coupling agent can also form chemical bonds with the capsule core material, thereby increasing the bonding between the capsule wall and the capsule core. The silane coupling agent can improve the bonding interface, reduce the incompatibility of the interface, and ensure the long-term stability and durability of the overall structure.

[0028] 5. The present invention adds an emulsifier and a dispersant to evenly disperse the reaction mixture, prevent solid particles from agglomerating and settling, help form a uniform and stable emulsion, improve reaction efficiency, and ensure the size uniformity and coverage rate of the polymer microcapsules.

[0029] 6. The self-repairing polymer microcapsules prepared by the present invention can effectively repair microcracks generated on the surface and inside of organic waterproof materials, effectively giving organic waterproof materials self-repairing capabilities and extending their service life.

[0030] 7. The preparation method of the self-healing polymer microcapsules of the present invention is simple, efficient and has high economic benefits.

[0031] 8. The polymer capsule of the present invention is added to the organic waterproof material in an amount of 4-6% when used. Under normal conditions, the polymer capsule has good mechanical properties and chemical stability. Only when cracks appear in the organic waterproof material, the polymer capsule ruptures under the stress of the tip of the crack, releasing the highly absorbent resin in the capsule core. The highly absorbent resin can expand rapidly after contacting water, repair the cracks in time, and restore the integrity of the organic waterproof material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a microscopic image of the polymer capsule obtained in Example 1.

[0033] Figure 2 This is a microscopic image of the polymer capsule obtained in Example 2.

[0034] Figure 3 This is a microscopic image of the polymer capsule obtained in Example 3.

[0035] Figure 4 This is a microscopic image of the polymer capsule obtained in Example 4.

[0036] Figure 5 This is a microscopic image of the polymer capsule obtained in Example 5.

[0037] Figure 6 Microscope image of the polymer capsule obtained in Example 6.

[0038] Figure 7 This is a microscopic image of the polymer capsule obtained in Example 7.

[0039] Figure 8 This is a microscopic image of the polymer capsule obtained in Example 8. DETAILED DESCRIPTION

[0040] The specific implementation modes of the present invention are described below in conjunction with examples. However, the following examples are only used to illustrate the present invention in detail and are not intended to limit the scope of the present invention in any way.

[0041] In the following embodiments,

[0042] Embodiment 1:

[0043] A polymer capsule for self-repair of an organic waterproof material. The raw materials used are: 30 g of polytetramethylene glycol, 30 g of 2,4-toluene diisocyanate, 15 g of 1,4-butanediol, 15 g of highly absorbent resin, 50 g of polyethylene terephthalate, 30 g of Tween 40, 30 g of sodium alginate, 13 g of a silane coupling agent, 60 g of a methanol solution (35%), and 60 g of xylene.

[0044] The following steps were used for preparation:

[0045] 1) Weigh each raw material according to the amount;

[0046] 2) polytetrahydrofuran diol and 2,4-toluene diisocyanate were mixed, and stirred at 300 r / min and 85° C. for 8 min using a magnetic stirrer to uniformly mix and obtain a prepolymer for standby use;

[0047] 3) Add Tween 40 and sodium alginate into the methanol solution, stir at 300 r / min and 85°C for 8 min to mix well;

[0048] 4) adding the highly absorbent resin to the solution obtained in 3) and stirring at 300 r / min for 15 min to mix well;

[0049] 5) Add 1,4-butanediol to the solution obtained in 4) and stir at 300 rpm for 15 min to mix well;

[0050] 6) adding the prepolymer obtained in 2) to the solution obtained in 5) and stirring at 800 r / min for 2 h, filtering, washing the solid twice with deionized water, and drying to obtain particles A;

[0051] 7) Add polyethylene terephthalate to the organic solvent, stir at 800 r / min and 85° C. for 8 min, and mix well;

[0052] 8) adding the silane coupling agent to the solution obtained in 7), stirring at 800 r / min and 85° C. for 8 min, and mixing well;

[0053] 9) placing the particles A obtained in 6) into the solution obtained in 8) and continuing stirring for 1-3 hours. After filtration, the solid matter is placed in a forced air drying oven at 50° C. and dried for 20 hours to obtain a polymer capsule for self-repairing of an organic waterproof material.

[0054] Embodiment 2:

[0055] A polymer capsule for self-repair of an organic waterproof material. The raw materials used are: 20g of polytetramethylene glycol, 40g of 2,4-toluene diisocyanate, 10g of 1,4-butanediol, 20g of highly absorbent resin, 30g of polyethylene terephthalate, 40g of Tween 4040g, 20g of sodium alginate, 10g of a silane coupling agent, 80g of a methanol solution (30%), and 40g of xylene.

[0056] The preparation was carried out according to the preparation of Example 1.

[0057] Embodiment 3:

[0058] A polymer capsule for self-repair of an organic waterproof material. The raw materials used are: 40 g of polytetramethylene glycol, 20 g of 2,4-toluene diisocyanate, 20 g of 1,4-butanediol, 10 g of highly absorbent resin, 60 g of polyethylene terephthalate, 20 g of Tween 40, 40 g of sodium alginate, 15 g of a silane coupling agent, 50 g of a methanol solution (40%), and 80 g of xylene.

[0059] The preparation was carried out according to the preparation of Example 1.

[0060] Embodiment 4:

[0061] A polymer capsule for self-repair of an organic waterproof material. The raw materials used are: 35 g of polytetramethylene glycol, 35 g of 2,4-toluene diisocyanate, 20 g of polyethylene glycol, 15 g of highly absorbent resin, 60 g of polyethylene terephthalate, 20 g of Tween 40, 20 g of sodium alginate, 15 g of a silane coupling agent, 50 g of a methanol solution and 70 g of xylene.

[0062] The preparation was carried out according to the preparation of Example 1.

[0063] Embodiment 5:

[0064] A polymer capsule for self-repair of an organic waterproof material. The raw materials used are: 30 g of polytetramethylene glycol, 30 g of 2,4-toluene diisocyanate, 15 g of 1,4-butanediol, 15 g of super absorbent resin, 50 g of polyethylene terephthalate, 30 g of Tween 40, 30 g of sodium alginate, 60 g of methanol solution and 60 g of xylene.

[0065] The preparation method is different from Example 1 in that step 8) is omitted, the particles obtained in step 6 are placed in the solution obtained in step 7), stirring is continued for 1-3 hours, and the solid matter after filtration is placed in a forced air drying oven at 40-60°C for 12-24 hours to obtain a polymer capsule for self-repairing of an organic waterproof material.

[0066] Embodiment 6:

[0067] A polymer capsule for self-repairing of an organic waterproof material. The raw materials used are: 30 g of polytetramethylene glycol, 30 g of 2,4-toluene diisocyanate, 15 g of a highly absorbent resin, 50 g of polyethylene terephthalate, 30 g of Tween 40, 30 g of sodium alginate, 13 g of a silane coupling agent, 60 g of a methanol solution, and 60 g of xylene.

[0068] The difference from Example 1 is that step 5) is missing.

[0069] Embodiment 7:

[0070] A polymer capsule for self-repair of an organic waterproof material. The raw materials used are: 30 g of polytetramethylene glycol, 30 g of 2,4-toluene diisocyanate, 15 g of 1,4-butanediol, 15 g of super absorbent resin, 50 g of polyethylene terephthalate, 30 g of Tween 40, 30 g of sodium alginate, 13 g of a carboxylic acid functional group coupling agent, 60 g of methanol solution, and 60 g of xylene.

[0071] The preparation was carried out according to the preparation of Example 1.

[0072] Embodiment 8:

[0073] A polymer capsule for self-repairing of an organic waterproof material. The raw materials used are: 30 g of polytetramethylene glycol, 30 g of 2,4-toluene diisocyanate, 15 g of 1,4-butanediol, 15 g of super absorbent resin, 30 g of Tween 40, 30 g of sodium alginate, 13 g of a silane coupling agent, 60 g of a methanol solution, and 60 g of xylene.

[0074] The difference from Example 1 is that step 7) is missing.

[0075] The electron micrographs of the polymer capsules obtained in Examples 1-8 are as follows: Figure 1-8 As shown, the capsules prepared in Examples 1-4 are uniform in size and spherical, with good sphericity and a dense surface, and the capsule morphology of Example 1 is the best. The polymer capsules obtained in Examples 5-7 are far less effective than those in Examples 1-4, with poor uniformity in capsule size and sphericity. The size of the capsules prepared in Example 8 is significantly smaller than that of Examples 1-7, with uneven capsule size and poor sphericity.

[0076] The sizes and coverage ratios of the polymer capsules obtained in Examples 1-8 are shown in Table 1 below:

[0077] Group Capsule size / μm Coverage rate / % Example 1 116 77.6 Example 2 105 72.6 Example 3 106 75.2 Example 4 108 74.5 Example 5 99 67.3 Example 6 90 63.8 Example 7 101 69.4 Example 8 75 62.1

[0078] As can be seen from the table, the capsule sizes of Examples 1-4 are slightly larger than the capsule sizes of Examples 5-7 without coupling agent, chain extender, or with other coupling agents, and are significantly larger than the single-shell capsules of Example 8. In addition, the coverage rates of polymer capsules prepared without adding silane coupling agent, without chain extender, or with other coupling agents are all lower than those of Examples 1-4.

[0079] In addition, the microcapsules should have sufficient mechanical strength and stability to withstand the shear stress generated during mixing and coating. The microcapsules should not break during mixing and coating. When cracks occur in the organic waterproofing material, they should break and release the repair material. 100 microcapsules per example were mechanically stirred at 200 rpm in mineral turpentine oil (MTO) at 40°C, and the samples were observed under an optical microscope after stirring for 20 minutes, and the number of microcapsule ruptures was counted.

[0080] The number of ruptures and capsule stability of the polymer capsules obtained in Examples 1-8 are shown in Table 2 below:

[0081]

[0082]

[0083] It can be seen from Table 2 that the number of microcapsules broken in Examples 1-4 is significantly less than that in Examples 5-8, and the number of single-layer wall microcapsules broken in Example 8 after stirring for 20 minutes is the largest, indicating that the single-layer wall microcapsules have the worst mechanical stability after being subjected to shear stress. The microcapsules prepared using coupling agents and chain extenders have better mechanical stability, and the mechanical stability of microcapsules prepared using silane coupling agents is better than that of microcapsules prepared using carboxylic acid functional group coupling agents.

[0084] The polymer capsules (40 g) obtained in Examples 1-8 were respectively mixed into asphalt waterproof materials (1000 g) in an amount of 4% of the mass of the waterproof material, and they were recorded as Application Examples 1-8 respectively. Control example: Asphalt waterproof coating without self-healing polymer capsules. The asphalt waterproof materials of each experimental group were cast into two sets of ductility test molds at the same time. According to the T0605 test procedure, the two sets of asphalt test molds were scraped flat, and one set of test pieces was cut from the middle with a blade to a fixed depth. The incised asphalt test pieces were placed at room temperature for 24 hours to allow them to heal themselves. Ductility tests were carried out on the two sets of test molds, and the ductility value L1 of the normal asphalt test piece and the ductility value L2 of the healed test mold were obtained respectively. In order to quantify the comparative analysis, the evaluation index of the healing ability of asphalt is defined as follows: Wherein, L1 is the elongation after fracture healing; L2 is the elongation of the complete specimen. Then, the asphalt coatings prepared in Examples 1-6 and the control example were taken as test objects, and each group of asphalt coatings was applied on three groups of identical test pieces, which were subjected to a pressurized anti-seepage test. The specific detection steps and detection standards refer to GB / T 23445-2009 "Polymer Cement Waterproof Coatings". When two of the three groups of test pieces show water permeability, it is recorded as "yes", and if not, it is recorded as "no". The healing rate and anti-seepage performance of the organic waterproof material (asphalt) obtained by using Examples 1-8 and the control example are shown in Table 3 below:

[0085]

[0086] As shown in Table 3, the control example has water seepage at a penetration pressure of 0.3Mpa. The healing rate and anti-seepage performance of the asphalt waterproof material obtained by adding Examples 1-8 are improved. The healing rate and anti-seepage performance of the asphalt waterproof material adding the polymer microcapsules of Examples 1-4 are significantly better than the asphalt waterproof material adding the polymer capsules of Examples 5-8. Examples 5-8 have water seepage to varying degrees when the penetration pressure increases. The performance of the polymer microcapsules added in Examples 1-4 is relatively ideal, and the performance of the polymer microcapsules of Example 1 is the best. The reason is that the addition of silane coupling agent can increase the bonding stability between the inner wall and the outer wall. Compared with no coupling agent and single-shell structure capsules, the structure of the capsule can be made more stable, preventing the capsule from failing when mixed with the organic waterproof material.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A polymer capsule for self-repair of organic waterproof materials, characterized in that: The raw materials used are, by weight, 20-40 parts of polytetrahydrofuran diol, 20-40 parts of 2,4-toluene diisocyanate, 10-20 parts of chain extender, 10-20 parts of highly absorbent resin, 30-60 parts of polyester resin, 20-40 parts of emulsifier, 20-40 parts of dispersant, 10-15 parts of coupling agent, 50-80 parts of methanol solution and 40-80 parts of organic solvent.

2. The polymer capsule for self-repairing of organic waterproof material according to claim 1, characterized in that: The size of the polymer capsules is 100-300 microns.

3. The polymer capsule for self-repairing of organic waterproof material according to claim 1 or 2, characterized in that: The chain extender is one or more of 1,4-butanediol, 1,6-hexanediol and polyethylene glycol.

4. The polymer capsule for self-repairing of organic waterproof material according to claim 1 or 2, characterized in that: The component of the highly water-absorbent resin is polyacrylamide; the polyester resin is one or more of polyethylene terephthalate and polybutylene terephthalate.

5. The polymer capsule for self-repairing of organic waterproof material according to claim 1 or 2, characterized in that: The emulsifier is one or more of gum arabic, Span 40, Span 60, Tween 20, Tween 40, and polyvinyl alcohol; the dispersant is sodium alginate; the coupling agent is a silane coupling agent; and the organic solvent is one or more of xylene, acetone, and toluene.

6. The polymer capsule for self-repairing of organic waterproof material according to claim 1 or 2, characterized in that: The concentration of the methanol solution is 30%-40%.

7. A method for preparing the polymer capsule for self-repairing of organic waterproof material according to claim 1, characterized in that: The following steps are involved: 1) Weigh each raw material according to the proportion; 2) polytetrahydrofuran diol and 2,4 toluene diisocyanate are mixed and prepared as performed polymer for standby use; 3) Add emulsifier and dispersant into methanol solution and mix well; 4) adding the highly absorbent resin to the solution obtained in 3) and mixing well; 5) adding the chain extender to the solution obtained in 4) and mixing; 6) adding the prepolymer obtained in 2) to the solution obtained in 5) and stirring, filtering, washing and drying to obtain particles A; 7) Add the polyester resin into the organic solvent and mix well; 8) adding the coupling agent to the solution obtained in 7) and mixing; 9) placing the particles A obtained in 6) in the solution obtained in 8) and continuing stirring, filtering and drying the solid matter to obtain a polymer capsule for self-repairing of an organic waterproof material.

8. The preparation method according to claim 7, characterized in that: In the step 6) and step 9), the drying is carried out at 40-60° C. for 12-24 hours.